(untitled) (Journal of Special Education and Rehabilitation, 2014)
On the occasion of 3rd December – International day of persons with disabilities, this year as well, a ceremony was held at the Faculty of Philosophy, which was organized by the Institute of Special Education and Rehabilitation. The main focus was the creation of inclusive society, in accordance with this year’s theme of the day, set by the United Nations: Break Barriers, Open Doors for an inclusive society and development for all. In the official part of the program speeches were given by the Head of the Institute of Special Education and Rehabilitation, Zora Jachova, PhD, the Rector of the University “Ss. Cyril and Methodius” – Skopje, Velimir Stojkovski, Phd, the Minister for Education and Science, Mr. Spiro Ristovski and the Minister for Labor and Social Politics, Mr. Dime Spasov. Their speeches stressed the activities done so far in their own field of work and also addressed the further plans in the area of education, social care and involvement of the persons with disabilities in all aspects of social life. One part of the program was intended for award, which was received by Martina Naumovska this year for the generation awarding by The Foundation Prof. Dr Ljupco Ajdinski. This year, beside the Best student 2008/2009, there was an award for the highest ranked student at the university admission in 2013/2014. This award was given to the student Ivana Brcheska. In the entertaining part of the ceremony, the students from DUCOR “Partenija Zografski” from Skopje and the students from OU “Dimo Hadzi Dimov” from Skopje – model school for inclusive practice participated. The students from “Partenija Zografski” performed two musical appearances accompanied with the sign language translation, by their musical-stage performance they shared the message of equality and breaking communication barriers between people. The students from “Dimo Hadzi Dimov” additionally enriched the program by performing a recitation and humorous play script. At the end, the guests were entertained by Gjoko Taneski, who performed 3 of his songs. After his performance, the ceremony was closed with the call for mutual contribution in promoting the inclusive culture in Republic of Macedonia.